Structural Interpretation of the Jonggol Mount Area, Kulon Progo, Yogyakarta, Using Gravity Inversion Modelling - Setyo Pambudi; Rizqi Prastowo; Ajimas Pascaning Setiahadiwibowo (Jurusan Fisika FMIPA Universitas Andalas, 2026)
The Mount Jonggol region in Kulon Progo, Yogyakarta, constitutes an important segment of the Sunda–Banda magmatic arc system; however, its subsurface structural configuration remains insufficiently understood. This study aims to interpret subsurface structures and lithological boundaries through derivative analysis and three-dimensional gravity inversion modelling. The gravity dataset was obtained from the Global Gravity Model Plus (GGMplus), which provides absolute gravity acceleration measurements with high spatial resolution. The data were processed using sequential corrections, including normal gravity, free-air, simple Bouguer, and terrain corrections, to generate the Complete Bouguer Anomaly (CBA). The resulting CBA data were analyzed using the First and Second Horizontal Derivative (FHD and SHD) methods to delineate structural discontinuities, fault planes, and density contrasts. Furthermore, three-dimensional inversion modelling was conducted to visualize subsurface density variations to a depth of approximately 3.5 km. The results indicate that Mount Jonggol is situated at the tectono-lithological boundary between the low-density Jonggrangan Formation (2.0–2.4 g/cc) and the high-density Old Andesite Formation (2.7–3.0 g/cc). The gravity anomaly pattern reveals a northwest–southeast-oriented magmatic corridor controlled by thrust and strike-slip fault systems, providing important insights into the tectono-magmatic evolution and uplift mechanisms of southern Central Java.